2017
DOI: 10.1016/j.colsurfb.2017.07.055
|View full text |Cite
|
Sign up to set email alerts
|

Oil-based cyclo-oligosaccharide nanodevices for drug encapsulation

Abstract: New encapsulation nanodevices were synthesized by emulsification of cyclo-oligosaccharides fully substituted by hydrophobic palmitic chains. These highly hydrophobic compounds, acquire oily-like behaviour at moderate temperatures (∼50°C) and when submitted to ultrasound (US) can undergo emulsification. The improved emulsifying properties of modified cyclo-oligosaccharides are suitable to produce small and narrow sized nanoemulsions with ability to encapsulate amphiphilic molecules. Both encapsulation and deliv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 29 publications
(40 reference statements)
0
2
0
Order By: Relevance
“…Cells and culture conditions. BJ5ta cell line was grown as previously reported (Noro et al, 2017). Caco-2 cells were grown similarly as BJ5ta, but using only Dulbecco's Modified Eagle's Medium (DMEM) supplemented with 20% (v/v) of fetal bovine serum (FBS); 1% (v/v) of penicillin/streptomycin solution and 1% (v/v) of Minimum Essential Medium (MEM) nonessential amino acids, as previously described (Loureiro et al, 2015a).…”
Section: Encapsulation Efficiencymentioning
confidence: 99%
See 1 more Smart Citation
“…Cells and culture conditions. BJ5ta cell line was grown as previously reported (Noro et al, 2017). Caco-2 cells were grown similarly as BJ5ta, but using only Dulbecco's Modified Eagle's Medium (DMEM) supplemented with 20% (v/v) of fetal bovine serum (FBS); 1% (v/v) of penicillin/streptomycin solution and 1% (v/v) of Minimum Essential Medium (MEM) nonessential amino acids, as previously described (Loureiro et al, 2015a).…”
Section: Encapsulation Efficiencymentioning
confidence: 99%
“…The use of high energy systems, like sonication, for the formation of micelles and nanoemulsions is a well explored methodology (Kumar and Kumar, 2018;Loureiro et al, 2016;Noro et al, 2017;Yusof and Ashokkumar, 2015), although no reports have been found describing the use of this method for the formation of PTS micelles. We investigated the application of sonication, mainly aiming to avoid the use of an organic solvent in the system.…”
Section: Micelles Productionmentioning
confidence: 99%